Kesenjangan Kompetensi Lulusan Pendidikan Keagamaan Katolik: Studi Kasus Perspektif Alumni dan Pengguna di Sekolah Tinggi Katolik Santo Yakobus Merauke - Pranyoto, Yohanes Hendro; Berangka, Dedimus (Kariwari: Jurnal Pendidikan Agama Katolik dan Pastoral, 2025)
This research analyzes the competency gaps among graduates of the Catholic Religious Education Study Program at Saint James Catholic College of Merauke from both alumni and user perspectives. Employing a case study design with descriptive qualitative approach supported by quantitative data, the study involved 45 alumni from the 2020-2024 graduation period and 45 graduate users in South Papua. Data collection was conducted through structured surveys, in-depth interviews, and documentation studies. Research findings reveal significant competency gaps in digital skills (-24.5%), multicultural communication (-18.3%), and pastoral leadership (-15.5%), while pastoral catechetical competency demonstrates a solid foundation with the smallest gap (-4.3%). Contributing factors include curriculum limitations that have not been responsive to technological developments, limited technology infrastructure, and post-pandemic digital transformation creating new competency demands. The dispersed geographical conditions of South Papua with the multicultural complexity of 20 ethnic groups add challenges for graduates in integrating Catholic values with local wisdom. Despite relatively high user satisfaction levels (4.51 on a scale of 5), there has been an increased demand for digital competency by 45%, social advocacy skills by 42%, and conflict management by 38% during 2020-2024. The research recommends responsive curriculum development, technology infrastructure strengthening, enhanced strategic partnerships with user institutions, and continuous professional development programs to bridge competency gaps.